The Effect of Religiusity, Halal Label, Brand Image and Celebrity Endorser on Purchase Decisions on Shampo Hijab Products (The Case of Muslim Consumer Study in Semarang) - Victorio Aqsa Falajabudien; Fuad Mas'ud (AFEBI Islamic Finance and Economic Review, 2020)
The demand for halal products is mandatory for every Muslimah, including halal hijab shampo products. This study aims to determine the effect of religiosity, halal label, brand image, and celebrity endorser as independent variables in this study on purchasing decisions for hijab shampo products, which are the dependent variable. The data collection method was done through a questionnaire. The population in this study are Muslim consumers who have bought and used shampo hijab products in the city of Semarang. This study selected a sample of 100 respondents using a purposive sampling approach. The data are then analyzed using multiple linear regression analysis techniques. The results of the analysis show that the halal label and brand image variables have a positive and significant effect on purchasing decisions, while the religiosity and celebrity endorser variables have no significant effect on purchasing decisions. Simultaneously, the results of the independent variable religiosity, halal label, brand image and celebrity endorser have a simultaneous effect on purchasing decisions.Keywords: Religiosity; halal label; brand image; celebrity endorser; purchase decision